The neuroprotective effects of activated α7 nicotinic acetylcholine receptor against mutant copper–zinc superoxide dismutase 1-mediated toxicity - Taisei Ito (Nature Portfolio, 2020)
Abstract Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the selective and progressive loss of motor neurons. Although many drugs have entered clinical trials, few have shown effectiveness in the treatment of ALS. Other studies have shown that the stimulation of α7 nicotinic acetylcholine receptor (nAChR) can have neuroprotective effects in some models of neurodegenerative disease, as well as prevent glutamate-induced motor neuronal death. However, the effect of α7 nAChR agonists on ALS-associated mutant copper–zinc superoxide dismutase 1 (SOD1) aggregates in motor neurons remains unclear. In the present study, we examined whether α7 nAChR activation had a neuroprotective effect against SOD1G85R-induced toxicity in a cellular model for ALS. We found that α7 nAChR activation by PNU282987, a selective agonist of α7 nAChR, exhibited significant neuroprotective effects against SOD1G85R-induced toxicity via the reduction of intracellular protein aggregates. This reduction also correlated with the activation of autophagy through the AMP-activated protein kinase (AMPK)–mammalian target of rapamycin (mTOR) signaling pathway. Furthermore, the activation of α7 nAChRs was found to increase the biogenesis of lysosomes by inducing translocation of the transcription factor EB (TFEB) into the nucleus. These results support the therapeutic potential of α7 nAChR activation in diseases that are characterized by SOD1G85R aggregates, such as ALS.